1998
DOI: 10.1172/jci3949
|View full text |Cite
|
Sign up to set email alerts
|

A gender-related defect in lipid metabolism and glucose homeostasis in peroxisome proliferator- activated receptor alpha- deficient mice.

Abstract: The peroxisome proliferator-activated receptor ␣ (PPAR ␣ ) is a nuclear receptor implicated in the control of cellular lipid utilization. To test the hypothesis that PPAR ␣ is activated as a component of the cellular lipid homeostatic response, the expression of PPAR ␣ target genes was characterized in response to a perturbation in cellular lipid oxidative flux caused by pharmacologic inhibition of mitochondrial fatty acid import. Inhibition of fatty acid oxidative flux caused a feedback induction of PPAR ␣ ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
284
0
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 385 publications
(308 citation statements)
references
References 26 publications
22
284
0
2
Order By: Relevance
“…Perhaps other pathways that are not directly controlled by HNF1α may contribute to the sex-specific phenotype. For example, it was suggested that estrogen may play a role in the regulation of fatty acid utilization pathways affecting both cardiac and hepatic lipid homeostasis (23). In PPARα-deficient mice, a pharmacological inhibition of mitochondrial fatty acid import by the drug etomoxir resulted in massive hepatic and cardiac accumulation, hypoglycemia, and death in 100% of male, but only 25% of female PPARα-null mice (23).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps other pathways that are not directly controlled by HNF1α may contribute to the sex-specific phenotype. For example, it was suggested that estrogen may play a role in the regulation of fatty acid utilization pathways affecting both cardiac and hepatic lipid homeostasis (23). In PPARα-deficient mice, a pharmacological inhibition of mitochondrial fatty acid import by the drug etomoxir resulted in massive hepatic and cardiac accumulation, hypoglycemia, and death in 100% of male, but only 25% of female PPARα-null mice (23).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, impaired upregulation of PDK4 protein expression, resulting in an inappropriately high PDK2-to-PDK4 activity ratio, could result in increased flux via PDC at the expense of entry of pyruvate into gluconeogenesis. Support for this possibility comes from studies of peroxisome proliferator-activated receptor-␣ (PPAR␣)-null mice where pharmacological inhibition of mitochondrial FA oxidation results in severe hypoglycemia (7). Upregulation of PDK2 protein expression, in addition to that of PDK4, in liver after prolonged starvation may subserve a further function in that it could permit activation of PDC should pyruvate accumulate.…”
Section: Functional Significance Of Pdk Isoform Shiftsmentioning
confidence: 99%
“…Like PPAR␥, PPAR␣ has a hypolipidemic action. However, in this case, the lipid-lowering effect results from enhanced FA uptake, activation, and oxidation by tissues other than white adipose tissue (4,6,7,12,33,62,63). Because of the clear correlation between altered lipid homeostasis and tissue PDK4 protein expression and the resulting impact that this might have on rates of glucose oxidation, much current interest has been focused on the potential regulation of PDK4 expression by PPAR␣.…”
Section: Regulation Of Mammalian Pdk4 Expression By Pparsmentioning
confidence: 99%
“…In contrast, PPAR␣ Ϫ/Ϫ mice do not exhibit the expected fasting-mediated induction of most FAO enzyme genes, but instead develop hypoglycemia, exhibit inadequate ketogenesis, accumulate neutral lipid in both heart and liver, and have a high death rate relative to wild-type mice (1). In addition, metabolic inhibition experiments and studies of senescent PPAR␣ Ϫ/Ϫ mice implicate PPAR␣ in the cardiac and hepatic lipid homeostatic response (10,13,14). Finally, PPAR␣ expression and activity are induced by physiologic stimuli known to increase energy demand and mitochondrial oxidative flux such as electrical activation of canine skeletal muscle (15) and in humans subjected to a course of endurance training (16).…”
mentioning
confidence: 99%
“…PPAR␣ is ligand-activated by a variety of natural and synthetic agonists, including arachidonic acid derivatives, fibrates, and long-chain fatty acids: metabolic substrates for cardiac FAO enzymes. The important role played by PPAR␣ in cardiac metabolism is underscored by the marked reduction in the basal level of cardiac FAO enzyme gene expression in PPAR␣ Ϫ/Ϫ mice (10,11), leading to reduced long-chain fatty acid uptake and oxidation (12).…”
mentioning
confidence: 99%